Using system dynamics to illustrate deming’s system of profound knowledge - Stepanovich, Paul L (Total Quality Management & Business Excellence, 2004)
This article presents a systems dynamics model to illustrate some of the aspects of Deming's System of Profound Knowledge. As a pedagogical tool, it would serve as a useful introduction for those new to Deming's ideas. It not only introduces the main parts of his system, but also highlights their interconnectedness. The model environment, an interactive management flight simulator, and the model content combine to provide several learning opportunities. The model uses the assumptions of regression to the mean, the 80:20 Rule, random walks, and learned helplessness to present a theory of how, managers learn to reduce quality in organizations. Those interested in exploring or teaching Deming's System can use the model as a launching point from which to explore the system further. Running the simulation provides an opportunity to identify and challenge assumptions, explore the harmful effects of tampering, examine the fundamental attribution error, develop control charts, and challenge the application of behaviourism in management.
Keywords: Deming; Pedagogy; Quality; System dynamics; dept.mgt